Leveraging business modeling tools for ecosystemic business model design - Christian Vorbohle; Dennis Kundisch (Journal of Business Models (JOBM), 2024)
Business modeling tools are crucial for designing and implementing successful business models. However, there exist instances-which we refer to as the design of ecosystemic business models-in which developing a business model requires simultaneous consideration of both one's own business model and that of ecosystem partners. In these instances, standard business modeling tools focusing on representing business models in isolation may be inadequate. Based on a real-world example of a business ecosystem from the maritime logistics industry, we highlight five significant design challenges for ecosystemic business models. We then reflect on and discuss the extended role of the business model as an instrument for inter-organizational alignment, and draw out three implications for business modeling tools. The objective of this paper is to deduce implications and functional design requirements for business modeling tools from a conceptual perspective.
Keywords: 650; Business Model Representations; Business Ecosystems; Conceptual Design Requirements